Image on Municipal Road Construction in Kenya and Nigeria: The Politics of Infrastructure Development (Image taken in Kaduna) - Yakubu, Moses; Attoh, Franca (Municipal Road Construction in Kenya and Nigeria: Investigating the Politics of Infrastructure Development, 2021)
Image of the interview from Kaduna, Kaduna State
Keywords: Municipal engineering; Construction; Infrastructure (Economics); Marginalised Communities; Infrastructure Development; Municipal Road; Nigeria; Kenya